Effect of a hyaluronic acid and carboxymethylcellulose ophthalmic solution on ocular comfort and tear‐film instability after cataract surgery. Issue 8 (August 2015) - Mencucci, Rita; Boccalini, Carlotta; Caputo, Roberto; Favuzza, Eleonora
Abstract : Purpose : To evaluate the efficacy and safety of using sodium hyaluronate 0.1% and carboxymethylcellulose 0.5% artificial tears for ocular discomfort and tear‐film stability in eyes after cataract surgery. Setting : Twenty ophthalmic centers in Italy. Design : Prospective randomized case series. Methods : This study enrolled patients scheduled for unilateral cataract surgery. After surgery, patients received artificial tears and a topical steroid–antibiotic (study group) or topical steroid–antibiotic alone (control group) and were assessed postoperatively at 1 and 5 weeks. Outcome measures were tear breakup time (TBUT), ocular surface disease index (OSDI), frequency of dry‐eye symptoms evaluated using a visual analog scale (VAS), and corneal fluorescein staining. Results : The study comprised 282 patients. At 5 weeks, the mean TBUT was statistically significantly higher in the study group than in the control group ( P = .0003). The mean OSDI score statistically significantly improved in both groups from 1 to 5 weeks ( P < .0001 for both groups); however, there was no statistically significant difference between the groups at these timepoints. The artificial tears statistically significantly improved VAS‐assessed dry‐eye symptoms in the study group compared with the control group at 5 weeks ( P < .001). The mean corneal fluorescein staining was significantly reduced in the study group compared with the control group at 5 weeks ( P = .002 versus P = .05, respectively). No treatment‐related adverse events were reported. Conclusion : Sodium hyaluronate 0.1% and carboxymethylcellulose 0.5% ophthalmic solution was effective and well tolerated in reducing dry‐eye disease symptoms and improving the clinical outcome after cataract surgery. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.